Lactobacillus spp. associated with early childhood caries - Svec, P; Sedlácek, I; Zácková, L; Nováková, D; Kukletová, M (Folia microbiologica, 2009)
A group of 69 lactobacilli was isolated from caries lesions and root canals of early childhood caries (ECC) affected children treated in the Department of Pedodontics (Children's Teaching Hospital, Brno, Czech Republic). Biochemical and physiological properties of all strains were characterized by API 50 CH kit and conventional tube tests. The rep-PCR fingerprinting with the (GTG)(5) primer was used for genotypic grouping of the isolates. The (GTG)(5)-PCR fingerprinting grouped all analyzed strains into a few clusters in nearly full agreement with phenotype identification results and clarified the taxonomic position of 13 biochemically unidentified strains. In total, 20 strains of Lactobacillus fermentum, 17 L. rhamnosus, 14 L. casei/paracasei, 7 L. gasseri, 7 L. salivarius and 4 L. plantarum were identified. Mixtures of two or even three Lactobacillus spp. were isolated from a few root canal content samples. Results obtained by biotyping and (GTG)(5)-PCR were generally comparable except for L. gasseri strains that were not biochemically identified. The (GTG)(5)-PCR fingerprinting was shown to be quicker, easier to perform and more reliable than biotyping. Our results imply this molecular method as a good tool for screening and identification of Lactobacillus spp. inhabiting dental plaque.
Keywords: zubní kaz; Dental Caries; DNA fingerprinting; DNA primery; Humans; DNA Primers; Bacterial Typing Techniques; fylogeneze; Lactobacillus; techniky typizace bakterií; Child; Czech Republic; dítě; lidé; DNA Fingerprinting; Phylogeny; Česká republika